The best incubation time for primary productivity of phytoplankton in Laguna Lake, North Maluku, Indonesia - YULIANA YULIANA; MUHAMMAD IRFAN (Biodiversitas Journal of Biological Diversity, 2018)
Yuliana, Irfan M. 2018. The best incubation time for primary productivity of phytoplankton in Laguna Lake, North Maluku, Indonesia. Biodiversitas 19: 1021-1028. Primary productivity of phytoplankton is a source of energy and organic matter utilized by organisms at higher food chain levels. The measurement of the high rate of primary productivity can be done through the incubation of sample water at a particular time and time depending on sunlight intensity. This study aimed to estimate the best incubation time to achieve the highest primary productivity of phytoplankton in Laguna Lake, Ternate City, North Maluku Province, Indonesia in February 2017. The study was conducted at one location with four different levels of depth of 0, 5, 10, and 15 meters, and at three incubation times, i.e., 09:00-13:00, 10:00-14:00, and 11:00-15:00 (Eastern Indonesian Time). The chemical and physical parameters of radiance, temperature, pH, nitrate, and orthophosphate content were measured to estimate water quality of the lake. The results of this study showed that were 10 genera of phytoplankton belonging to Bacillariophyceae (6 genera), Chlorophyceae (4 genera), and Cyanophyceae (2 genera). The Laguna Lake has temperature ranged between 29.0-31.1oC, nitrate content of 0.22-0.58 mg l-1, orthophosphate content of 0.14-0.27 mg l-1, and pH 7. The primary productivity value at incubation time 09:00-13:00; 10:00-14:00; and 11:00-15:00 were of 101,851-258,278; 40,59-351,643; and 76,197-305,754 mgC m-3 hours-1, respectively. The best incubation time that provides the highest value in the measurement of primary productivity of phytoplankton at Laguna Lake was at 10:00 am to 14:00 pm.